2009
DOI: 10.5038/2375-0901.12.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Actor Roles in the Service Development Process

Abstract: The purpose of this study is to increase understanding of the different actors participating in the service development process, the roles they play, and the resources they contribute to the process. The public transport system in Sweden is a complex setting in which many actors control a variety of resources. Using the established tripartite network model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…If the findings from this study are compared with other studies, we can see similarities in the previous studies that were carried out by Gottfridsson (2009) where a number of internal and external actors were identified that were based on the public transport sector. Even though there were similarities between these studies with respect to the existence of external and internal actors and actors' roles, there are still some differences between the actual function and resources that each of these actors fulfill and contribute.…”
Section: Inspirer or Supporting Actorssupporting
confidence: 64%
See 1 more Smart Citation
“…If the findings from this study are compared with other studies, we can see similarities in the previous studies that were carried out by Gottfridsson (2009) where a number of internal and external actors were identified that were based on the public transport sector. Even though there were similarities between these studies with respect to the existence of external and internal actors and actors' roles, there are still some differences between the actual function and resources that each of these actors fulfill and contribute.…”
Section: Inspirer or Supporting Actorssupporting
confidence: 64%
“…In a previous study Gottfridsson (2009) identified eight main categories of actors who were involved in the service-development processes in the public transport sector: 1 Strategy creators; 2 Competing actors; 3 Deciding actors; 4 Supporting actors; 5 Prime-movers; 6 Suppliers; 7 Service performer; and 8 Users.…”
Section: Actors In the Service-development Processmentioning
confidence: 99%
“…To further discuss the development, however, other researchers have introduced more groups of actors that are worth noting. Gottfridsson (2009) presented eight groups of actors related to the service development process. The eight groups were "the strategic creators, the competing actors, the deciding actors, the supporting actors, the prime movers, the suppliers, the service performers, and the users" [Gottfridsson, (2009), p.1].…”
Section: Impact Of Customer's Involvement On the New Service Developmmentioning
confidence: 99%
“…Gottfridsson (2009) presented eight groups of actors related to the service development process. The eight groups were "the strategic creators, the competing actors, the deciding actors, the supporting actors, the prime movers, the suppliers, the service performers, and the users" [Gottfridsson, (2009), p.1]. Gottfridsson grouped users as the internal key function, since they played two roles, i.e., the user and the co-producer.…”
Section: Impact Of Customer's Involvement On the New Service Developmmentioning
confidence: 99%
“…In some other cases, the ideas are not actually ideas as we would generally describe them; instead, they are more in the form of an expressed need for something to fix a certain problem or achieve a wanted position. These ideas do not origin from the minds of individual actors and are not necessarily creative per se; instead, they are strategically or politically driven and could be described as a central thought leading the service development process, and the initiator of the so-called idea could be an actor or group of actors that could be labeled as strategy creators (Gottfridsson, 2009). The outcome of such a process could be described as a service description rather than a creative idea (Gottfridsson, 2012).…”
Section: Introductionmentioning
confidence: 99%